2004
DOI: 10.1007/s00422-003-0434-6
|View full text |Cite
|
Sign up to set email alerts
|

The world from a cat?s perspective ? statistics of natural videos

Abstract: The mammalian visual system is one of the most intensively investigated sensory systems. However, our knowledge of the typical input it is operating on is surprisingly limited. To address this issue, we seek to learn about the natural visual environment and the world as seen by a cat. With a CCD camera attached to their head, cats explore several outdoor environments and videos of natural stimuli are recorded from the animals' perspective. The statistical analysis of these videos reveals several remarkable pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 67 publications
4
111
0
Order By: Relevance
“…Indeed, statistical properties of natural scenes as viewed by cats exhibit a bias for cardinal with prevalence for horizontal contours (Betsch et al, 2004). A bias for cardinal orientations is also found in human natural scenes (Nasr and Tootell, 2012).…”
Section: Anisotropy Between Network Linking Neurons Preferring Horizmentioning
confidence: 90%
“…Indeed, statistical properties of natural scenes as viewed by cats exhibit a bias for cardinal with prevalence for horizontal contours (Betsch et al, 2004). A bias for cardinal orientations is also found in human natural scenes (Nasr and Tootell, 2012).…”
Section: Anisotropy Between Network Linking Neurons Preferring Horizmentioning
confidence: 90%
“…Natural environments are characterized by large variation in contrast, a patchy distribution of objects and a pronounced depth structure. Nervous systems have evolved to compute behaviourally relevant information under such complex natural conditions in an efficient and robust way and their design is likely to reflect the statistical and dynamical properties of these conditions (Betsch et al 2004;Burton and Laughlin 2003;Eckert and Zeil 2001;Kayser et al 2004;Olshausen and Field 1996;Reinagel 2001;Simoncelli 2003;Simoncelli and Olshausen 2001;van Hateren 1997). Since the structure of the environment and the animal's own movements both determine the image motion pattern animals experience, the processing of natural optic flow can only be investigated from the viewpoint of the behaving animal (e.g.…”
Section: Neuronal Coding Of Natural Optic Flow: a Critical Assessmentmentioning
confidence: 99%
“…Betsch et al (2004) showed that the exploration strategy and the difference of vantage point of animals significantly altered the statistics of natural scenes. This is fully consistent with the lesson from the studies of visuo-tactile interfaces for blind people (see Bach-y-Rita and Kercel, 2003, for a review).…”
Section: Introductionmentioning
confidence: 99%